Numerical simulation of flashing jets atomisation using a unified approach. (April 2019) - Lyras, Konstantinos G.; Dembele, Siaka; Wen, Jennifer X.
Highlights: Flash-atomisation is investigated studying both the mechanical and thermodynamic effects that break-up the liquid jet. A unified Eulerian methodology is proposed for studying flashing jets simulating both the internal flow and the spray dynamics. The Eulerian-Lagrangian-Spray-Atomisation (ELSA) model is extended for simulating superheated jets. The atomisation model is coupled with a pressure equation which takes into account the non-equilibrium state of the fluid and surface tension. The model is used to predict various spray characteristics such as the Sauter mean diameter, the jet velocity and the spray angle. Abstract: The physics of the atomisation of flash boiling jets is known to be extremely complex with interactions of different mechanisms at microscopic and macroscopic level. Early studies describe both the mechanical and thermodynamic effects focusing on the influence of the initial pressure and temperature on the spray characteristics. The resulting flashing jet usually emerges to the low-pressure region with a high velocity and fragments to large blobs and ligaments which break up to droplets due to both mechanical and thermodynamic effects. This present study describes a numerical approach for simulating the atomisation of flashing liquids suitable for both primary atomisation and secondary break-up using the Eulerian-Lagrangian-Spray-Atomisation model coupled with a pressure equation for the metastable jet. The proposed approach aims at describing the atomisation of superheated jets and the impact of bubble nucleation at different stages and regimes inside the channel the liquid emerges from. The changes in the regime outside the nozzle are discussed for various cases of flashing liquids providing insights for the interactions of the mechanisms that contribute to the liquid fragmentation and the spray characteristics such as the droplet size and velocity and the spray angle.